Approved revenue, recurrent and capital estimates - Nigeria; Nigeria (Lagos : Federal Govt. Press, 1983)
Estimate of the government budget expenditure for the period of 1987.
aia 28/03/2019
Loans
Keywords: Budget; Revenue; Öffentlicher Haushalt; Nigeria; Budget; Expenditures, Public; Revenue; Nigeria; Nigeria